Sediment and Nutrient Retention Capacity of Natural Riverine Wetlands in Southwest Ethiopia - Mereta, Seid Tiku; De Meester, Luc; Lemmens, Pieter; Legesse, Worku; Goethals, Peter L. M.; Boets, Pieter (Frontiers in Environmental Science, 2020)
Although wetlands in temperate regions have been studied for their pollutant remediation potential, the sediment and nutrient retention capacity of natural wetlands in tropical environments remains understudied. In this study, a mass balance approach was used to estimate the amount of sediment and nutrients retained at 40 different study sites located in four natural riverine wetlands in Southwest Ethiopia. Awetu and Boye wetlands retained a substantial amount of total suspended solids (TSS) and nutrients whereas Kofe and Kito wetlands had a net release. Overall, the amount of TSS retained by the four wetlands was estimated to be 6266.5 kg/ha/day. On the other hand, the net retention of Total Organic Nitrogen (TON) and Total Phosphorous (TP) was estimated to be 37.6 kg/ha/day and 40.9 kg/ha/day respectively. A stepwise multiple regression analysis revealed that anthropogenic activities such as farming, grazing, waste dumping and clay mining were the main variables that negatively affected the retention of TSS and nutrients. Farming alone explained 58% of the variation in TSS retention and cattle grazing explained 25% of the variation in TON retention. Therefore, watershed management interventions considering the mitigation of anthropogenic activities could be considered to reduce sediment and nutrient input and release.